Religiusitas Budaya Sipakatau, Sipakalebbi, Sipakainge Dalam Perspektif Resiliensi Sosial Masyarakat Kristen Bugis Watansoppeng, Sulawesi Selatan - Gendolang, Nova Diah Ayu (Mahesa Research Center, 2023)
This article aims to examine the resilience of Christian community midst of Muslim majority based on concept resilience in ability to face, overcome and adapt from a human experience or bad events that have occurred such as religious threats. This writing uses theory resilience and theory of culture in concept of religiosity. This study uses qualitative methods conducting observations, interviews, and literature studies. The focus of research is on the Bugis Christian community as a resilience group in the Land of Bugis Watansoppeng, who is present in the midst of local culture in the form resilience through the Sipakatau, Sipakalebbi, Sipakinge culture. The Bugis community is better known for its Muslim religious identity, so that Islamic characteristics that are more inherent in the Bugis Watansoppeng land affect social, customary and cultural life, including the Sipakatau, Sipakalebbi, Sipakalebbi culture which is part of the Panggadereng system (customary rules that are considered noble). The culture of Sipakatau, Sipakalebbi, Sipakinge becomes a value that meaningful for both Islam and Christianity. The results of this study show that Sipakatau, Sipakalebbi, Sipakalebbi culture is attainment a form of resilience to the Christian community in Watansoppeng which greatly affects all aspects of life every Bugis person, including Christians, so this culture has a positive impact and a positive perspective Christian community as resilient people. adapt and experience social change in religion.